Securitization of Energy Security in Central Asia - Czywilis, Dariusz; Nita, Łukasz; Sobański, Jacek (The Copernicus Journal of Political Studies, 2018)
This paper reviews the contemporary theoretical approaches to the subjects of international security policy and energy security. Apart from discussing the theory of securitization, especially in context of a theoretical debate between representatives of political realism and constructivism, key research dilemmas, concerning the defining of energy security and crucial security threats, will be presented as well. Second part of the paper contains a short description of international politics in the Central Asia, with particular reference to presentation of politics of the regional political powers and the post-Soviet republics. It is followed by presentation of securitizing actions of those subjects taken in the field of energy security. Among presented contexts of those actions are following issues: development of drilling infrastructure, security of transport, conflicts concerning access to alternative energy sources and political power game in presented region. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762